AN ANALYSIS OF STUDENTS’ ERRORS IN SPEAKING PERFORMANCE - Rada, Kevin Sean (Universitas Muhammadiyah Lampung, 2023)
English is not the new subject for students, but it still needs a better preparation in order to make the teaching learning process to be conducted sucsessfully and to reach the quality target. There are many conditions to create a good bilingual Teaching program, the requirements which is in line such as Teacher as a model for the students, their knowledge and ability in implementing the subject in the class. In this reaserch the writer found that the problems encountered by the teachers and students in the bilingual class were: Students found difficulties in developing their four skills of English, most of non English teacher got difficulties in teaching materials using English as the medium of instruction. Based on the experiences above, the writer tried to present illustration of the situation, the problem and how to solve it. To improve the bilingual teaching, Based on the result of the research, the writer suggested to encourage teachers of bilingual class to attend the seminar of English teaching by any institution suitable for their subjects and the teacher should vary their teaching performances in presenting the materials to the students so that the subjects are more understandable by the students. The teacher should use various English textbooks which are suitable with their major to supplement the English textbooks that the students had already got.